2016
DOI: 10.1371/journal.pone.0163560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effects of Topical Estradiol Benzoate Application on Cutaneous Wound Healing in Ovariectomized Female Mice

Abstract: Estrogen promotes cutaneous wound healing in ovariectomized (OVX) female mice. However, the effects of topical estrogen application on wounds remain unclear. Therefore, the aim of this study was to compare the effects of topical estrogen application on wounds with standard treatment methods. Eight-week-old C57BL/6J female mice underwent OVX and received two full-thickness wounds four weeks later. Mice were divided into three groups: topical estradiol benzoate (EB) (0.75 μg/g/day) wound treatment, subcutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…The ovary is the main source of estrogen in the premenopausal period, and granulosa cells are the key cells to produce estrogen [ 36 , 37 , 38 , 39 , 40 ]. Estrogen is also synthesized in skin tissue [ 41 ], presenting a concept termed “intracrinology” [ 42 ]. Crucially, estrogen regulation depends on estrogen-metabolism enzymes, which include aromatase, catalyzing the conversion of androgens (including dehydroepiandrosterone (DHEA) and testosterone) to estrogens, as well as 17β-hydroxysteroid dehydrogenase 1 and 17β-hydroxysteroid dehydrogenase 2 converting estrone to estradiol [ 42 ].…”
Section: Estrogen and Estrogen Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovary is the main source of estrogen in the premenopausal period, and granulosa cells are the key cells to produce estrogen [ 36 , 37 , 38 , 39 , 40 ]. Estrogen is also synthesized in skin tissue [ 41 ], presenting a concept termed “intracrinology” [ 42 ]. Crucially, estrogen regulation depends on estrogen-metabolism enzymes, which include aromatase, catalyzing the conversion of androgens (including dehydroepiandrosterone (DHEA) and testosterone) to estrogens, as well as 17β-hydroxysteroid dehydrogenase 1 and 17β-hydroxysteroid dehydrogenase 2 converting estrone to estradiol [ 42 ].…”
Section: Estrogen and Estrogen Signalingmentioning
confidence: 99%
“…The action of these estrogen-like compounds on cells or tissues is far more complicated, although the main pathway might follow the classical ligand-mediated nuclear receptor signaling, such as estrogen receptors α and β (ERα and ERβ) located within the nuclei of target cells [ 46 , 47 ]. The absence of a ligand (estrogen) shows that ERs are associated with an inhibitory heat shock protein [ 41 ].…”
Section: Estrogen and Estrogen Signalingmentioning
confidence: 99%
“…A CD31 antibody has frequently been used to stain endothelial cells. 11,21,24,25 In this study, the results of paired measurements obtained from 2D ultrasound images with the Color Doppler mode and immunohistologically stained sections on day 14 after wounding showed that Pearson's correlation coefficients were r=0.927, 0.871, 0.717, and 0.913 for wounds 1, 2, 3, and 4, respectively, indicating a correlation. This result showed that a strong correlation for % vascularity was obtained between paired 2D ultrasound imaging with the Color Doppler mode and sections immunohistologically stained for the anti-CD31 antibody.…”
Section: Discussionmentioning
confidence: 54%
“…However, the current result showed that half of the wounds were not completely covered with a new epithelium on day 14 after wounding, although the wounds generally heal with scars until day 14 after wounding. [19][20][21] Therefore, a longitudinally evaluating the distribution of vascular growth over the course of healing is a valuable approach, it is necessary to confirm this limitation near the future. In summary, our results indicate that high-resolution 3D ultrasound imaging is useful for longitudinally evaluating the distribution of vascular growth over the course of healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation